1991
DOI: 10.1159/000292999
|View full text |Cite
|
Sign up to set email alerts
|

Second-Trimester Thyroid Function and Pregnancy Outcome in Mothers with Hyperthyroidism

Abstract: Thyroid function at 24–28 weeks gestation was compared between 26 mothers with hyperthyroidism (16 on antithyroid treatment and 10 in remission without treatment) and 15 normal pregnant controls. There was no difference in the total and free thyroxine (TT4 and FT4) or in the total and free triiodothyronine (TT3 and FT3) concentrations, but the erythrocyte zinc (RBC Zn) concentration was significantly lower in the study group (187.3 ± 46.6 µmol/l RBC versus 223.6 ± 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…The comparable NBW and prevalence of LBW among infants born to ET‐1, ET‐2 and healthy control mothers observed in our study suggests that the presence of hyperthyroidism during early and mid pregnancy might not affect NBW or the risk of LBW in the infants. Our observations disagree with that of Lao et al . (1991) who reported that NBW has significantly negative correlation with plasma concentration of total T3 in mothers with hyperthyroidism between 24 and 28 weeks of pregnancy ( r = − 0·5, P < 0·02).…”
Section: Discussioncontrasting
confidence: 99%
“…The comparable NBW and prevalence of LBW among infants born to ET‐1, ET‐2 and healthy control mothers observed in our study suggests that the presence of hyperthyroidism during early and mid pregnancy might not affect NBW or the risk of LBW in the infants. Our observations disagree with that of Lao et al . (1991) who reported that NBW has significantly negative correlation with plasma concentration of total T3 in mothers with hyperthyroidism between 24 and 28 weeks of pregnancy ( r = − 0·5, P < 0·02).…”
Section: Discussioncontrasting
confidence: 99%